Effect of upper limb focal muscle vibration on cortical activity: A systematic review with a focus on primary motor cortex - Kolbaşı, Esma Nur; Ersöz Hüseyinsinoğlu, Burcu; Bayraktaroğlu, Zübeyir (Wiley, 2022)
This systematic review aimed to investigate the effects of upper extremity focal muscle vibration (FMV) on cortical activity. A systematic literature search was conducted for articles published in English in the SCOPUS, PEDro, PUBMED, REHABDATA, MEDLINE, and Web of Science databases. Eighteen studies (6 controlled and 12 experimental studies) were included in the systematic review. A total of 264 individuals (20 to 68 years) participated in the studies. The outcome of this review showed that FMV might have contradictory effects on cortical areas: (a) Reduction of cortical activity in the primary motor cortex (M1) and somatosensory cortex (S1), (b) no changes in the cortical activity of M1, and (c) increased cortical activity of M1 and S1. These effects may depend on different factors such as frequency and amplitude of FMV, vibration exposure time, and muscle status. However, no single factor can definitely be accounted for the variance.
Keywords: Corticospinal Excitability; Motor Cortex; Somatosensory Cortex; Vibration